Searchable symmetric encryption - Thio, Brian Yu Li (Nanyang Technological University, 2020)
The paper aims to study the various Searchable Symmetric Encryption (SSE) schemes available [1,2,3,4,5] to understand the feasibility and efficiency of the schemes in helping to keep our data secure, when a huge amount of data is stored in a third-party cloud server. Each scheme tends to have a different profile of security leakage and efficiency, which can be attributed to the way the scheme is constructed. We first study some basic constructions to understand their respective weaknesses and strengths. Then, we develop the motivation to study a specific construction and its extension in depth. Next, we implement the Dynamic 2lev scheme related to the specific construction and study its efficiency in handling large datasets. From our results, we can conclude that the scheme is practical and efficient for data retrievals that does not require frequent updates. For tasks which requires frequent updating of the database, the Dynamic 2lev scheme might not be efficient as updating requires linear time. Hence, we proposed a possible solution of using distributed computing to improve the setup protocol within the algorithm to improve the efficiency scheme.